Verb movement and feature percolation: evidence from Turkish - Ulutaş, Süleyman. (Thesis (M.A.)-Bogazici University. Institute of Social Sciences, 2006., 2006)
This study discusses verb movement in Turkish in terms of itsmorphosyntactic and syntactic implications. The Turkish data suggest that themorphological selectional (i.e. m-selection) properties of the functional categories necessitate the head-movement of the lexical verb to the functional domain; that is,the functional categories in Turkish need to satisfy their m-selectional propertiesthrough the lexical verb or the verbal complex but when the lexical verb/verbalcomplex comes short of satisfying these constraints due to its participle nature, a verbal form (i.e. ol or i- copula) is inserted. However, independent of m-selectionalproperties of functional heads, there is substantial syntactic evidence suggesting thatthe verb moves to T head in Turkish since it not only interacts with object shift andNPI-licensing requirements but also affects the scope relations in a clause. When it moves, it not only expands the domain for the object but also checks the EPP featureof the T head. As a result of V-movement to T⁰, the object can scramble over thesubject as it is rendered equidistant to Spec TP position. Furthermore, the Turkishdata also present evidence to question the claim that V moves to C head (through T head); but instead, based on the data from such embedded structures as relativeclauses, a downward feature percolation from C head (i.e. C-to-T feature percolation)rather than an upward head movement (i.e. V-(to-T)-to-C movement) is proposed inthis study. The mechanism proposed sheds light on the Turkish relativization strategy on the basis of the percolation of FOC and AGR features from C⁰ to T⁰. In this way,the central role of the C head with respect to its featural composite is emphasized inthe present study.
Keywords: Turkish language -- Verb phrase.; Turkish language -- Syntax.; Turkish language -- Morphology.